KAJIAN LITERATUR EFEKTIVITAS GAYA KEPEMIMPINAN DEMOKRATIS DAN OTORITER SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Pramesthi, Riska Ayu; Windra, Ayu Dita; Hannan, Ainul; Puspita, Dini (Relawan Jurnal Indonesia, 2025)
This study examines the influence of democratic and authoritarian leadership styles on employee performance in an Indonesian organization or company. The method used in this study is a descriptive qualitative method referring to a literature review study. The author conducted research by analyzing various literature sources discussing the same topic, ranging from scientific journal articles, books, theses, and various other relevant literature to serve as references. The results of this study indicate that democratic leadership is more effective in increasing employee motivation, creativity, and loyalty through two-way communication and active participation. Meanwhile, authoritarian leadership remains relevant in situations that require high assertiveness and discipline. The effectiveness of both styles depends on the organizational context and employee characteristics. This study emphasizes the importance of implementing situational leadership that is adaptive to the needs and culture of modern work.